Análise das condições e modos de vida de mulheres em situação de rua em Porto Alegre-RS - Rosario, Graziela Oliveira do (2015)
The research presented here seeks to question the theme, the conditions and ways of life of woman who lives in streets in Porto Alegre – RS. It aims to be a study of experiences and social conditions of female contingent, through a gender approach. Sought to contribute to the production of knowledge in the area of social work on the issue of the homeless population in gender perspective. Guided by critical dialectical method, which it is a theoretical framework that enables the approach to reality aggregating the historicity categories, contradiction, totality and mediation in order to understand the phenomenon, since these are categories inherent in the study. It is understood that little quantity existence of studies that address the relationship genre / street show how this aspect is neglected, in spite of the advances made in recent decades in the female approach in expanding public policies to face the rualização processes. It is important to note that the discussion on gender does not include only the woman, but within the limits of a master's research, with limited time for its development, it was decided to seek to unveil the aspects that are transverse to the woman - street binomial, especially the womans on the streets of Porto Alegre city.